Evaluation of School Management Function within the Framework of New Public Management - Cajavilca Reyes, Katheryn (2024)
This essay aims to analyze the construction and consolidation of the performance evaluation of school principals as a tool of “New Public Management” and the consequences it can generate for these educational actors. To achieve this goal, within the framework of New Public Management and the theory of performativity, a review of international literature has been conducted. This review reveals that this type of evaluation has been expanding across various continents through specific public policies, signifying a global trend. Furthermore, it produces effects that impact the personal and professional lives of those undergoing evaluation.